Cost-utility analysis of interferon beta-1a (Avonex and Cinnovex) for relapsing remitting multiple sclerosis - Rahil Sadat Shahtaheri; Nahid Hatam; Zahra Goudarzi (Tehran University of Medical Sciences, 2018)
Background: Cinnovex is a biosimilar form of intramuscular (IM) interferon beta-1a (IFNβ-1a) manufactured in Iran for management of multiple sclerosis (MS). The present study aimed to determine the cost-utility of Cinnovex versus Avonex for patients with relapsing-remitting MS (RRMS) from Iranian health ministry perspective. Methods: A Markov model was developed to determine 10-year cost and quality-adjusted life-years (QALYs) of patients with transition through health states based on Kurtzke Expanded Disability Status Scale (EDSS). To estimate the cost of each method, we inquired the subsidies allocated to Avonex and Cinnovex by Iran's health ministry. Moreover, to estimate the quality of life (QOL) of patients in each group, a cross-sectional study was conducted among two groups of patients who had used Avonex and Cinnovex (n = 50 and n = 50, respectively), using the multiple sclerosis quality of life-54 (MSQOL-54) questionnaire. Finally, one-way sensitivity analysis (tornado diagram) was performed in order to examine the strength of the results. Results: According to results, the estimated 10-year discounted cost per patient for Avonex and Cinnovex were 21346.5 international dollar ($Int) and 47436.6 $Int, respectively; while the estimated total discounted QALYs per person were 3.76 and 3.89, respectively. The incremental cost per QALY for Cinnovex compared with Avonex was 162718.55 $Int. Conclusion: It is concluded that Cinnovex in patients with progressive relapsing MS is cost-effective associated with increased benefits compared with Avonex.